PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA DIGITAL MARKETING UNTUK MENINGKATKAN BRAND AWARENESS PADA USAHA MIKRO KECIL MENENGAH (UMKM): STUDI KASUS MACDUM - Camilia Fikhriyah,; Maria Salwa Humairoh,; Khansa Nabila Farahdini,; Nabila Tamara Hairani,; Rendi Panjaitan,; Hapsari Azzahra Widyarini,; Halimatus Sakdia,; Dea Ayu Silvia Ningrum,; Tri Siwi Agustina,; Elsa Yustika Putri, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Macdum is a home-based wheat macaroni snack business facing challenges in market expansion and limited digital marketing strategies. A four-month mentoring program was conducted to enhance brand awareness through social media and e-commerce-based digital marketing. The activities included reactivating social media accounts, conducting digital marketing training, redesigning packaging and introducing new product sizes, creating product catalogs and promotional posters, and selling through TikTok Shop and university cooperatives. Online marketing proved effective in increasing impressions, consumer engagement, and sales. Additionally, updating the business address on Google Maps strengthened the brand’s professional image. This study employed a qualitative descriptive method with an exploratory case study approach. The results show that integrating social media into marketing strategies is an efficient and impactful solution for MSMEs in the digital era. Recommendations were given to local governments and academics to provide broader support, training, and empowerment for MSMEs to become more adaptive and independent in facing market competition. This collaborative approach is expected to improve competitiveness and reinforce the existence of MSMEs like Macdum within the growing digital economy ecosystem